Atopic dermatitis, primary atopic disorders, and the cutaneous microbiome: current understanding of an expanding field - Abidov, Amir; Bayer, Diana K. (Frontiers in Pediatrics, 2025)
Atopic dermatitis is a common inflammatory skin disease with rapidly expanding worldwide prevalence. Increasingly, cases of severe and early-onset dermatitis have been identified and found to be due to underlying monogenic mutations, leading to immune dysregulation. These conditions, called primary atopic disorders, have become an area of extensive study over the last 30 years. Simultaneously, our understanding of the human microbiome has steadily grown, and there is clear evidence that dysbiosis plays a major role in atopic dermatitis, not only in severity of disease and as a potential trigger but also offering clues for targeted treatment strategies. Unfortunately, despite our growing understanding of the cutaneous microbiome and the expanding availability of genetic testing allowing for diagnosis of primary atopic disorders, there remains very limited understanding regarding the microbiomics changes that underlie these disorders. Here we review the current research regarding atopic dermatitis in the setting of primary atopic disorders, understanding regarding primary atopic disorders and associated cutaneous dysbiosis, and identify specific gaps in knowledge.